PENGUNGKAPAN TANGGUNG JAWAB SOSIAL BANK UMUM DI INDONESIA - Hafid Raihan Maulana; Yeni Oktaviani; Irma Novida; Aminudin Aminudin; Husnayetti Husnayetti; Adi Rizfalefriadi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
Corporate responsibility is not only to report the financial statements of each company annually but also for companies to address social responsibility and be able to contribute to the environment and the surrounding community. This study aims to determine the effect of Total Assets, Third Party Funds, and Equity on the Social Responsibility of Private Commercial Banks in Indonesia. The quantitative research design was used to analyze secondary data in the form of bank financial statements from 2016 to 2020. The research method uses panel data regression analysis. The results showed that the Total Assets partially had no significant effect on Social Responsibility with a t-count value of -1.547086 which was greater than t table 2.05553 with a significance value of 0.1245> 0.05. Third-Party Funds and Equity partially have a significant influence on Social Responsibility where the t-count value of Third-Party Funds is 2.903369 and the t-count Equity is 2.388913 greater than t table 2.05553 with a significance value of 0.006 and 0.004 <0.05. Simultaneously Total Assets, Third Party Funds, and Equity significantly influence Social Responsibility. It is proven that the calculated F value is 14,429 which is greater than the F table and the significance value of 0.00 is less than 0.05. Disclosure of corporate social responsibility is determined by the amount of Third Party Funds and the amount of company Equity